Diurnal variation in urodynamics of rat. - Gerald M Herrera; Andrea L Meredith (PLoS ONE)
In humans, the storage and voiding functions of the urinary bladder have a characteristic diurnal variation, with increased voiding during the day and urine storage during the night. However, in animal models, the daily functional differences in urodynamics have not been well-studied. The goal of this study was to identify key urodynamic parameters that vary between day and night. Rats were chronically instrumented with an intravesical catheter, and bladder pressure, voided volumes, and micturition frequency were measured by continuous filling cystometry during the light (inactive) or dark (active) phases of the circadian cycle. Cage activity was recorded by video during the experiment. We hypothesized that nocturnal rats entrained to a standard 12:12 light:dark cycle would show greater ambulatory activity and more frequent, smaller volume micturitions in the dark compared to the light. Rats studied during the light phase had a bladder capacity of 1.44+/-0.21 mL and voided every 8.2+/-1.2 min. Ambulatory activity was lower in the light phase, and rats slept during the recording period, awakening only to urinate. In contrast, rats studied during the dark were more active, had a lower bladder capacities (0.65+/-0.18 mL), and urinated more often (every 3.7+/-0.9 min). Average bladder pressures were not significantly different between the light and dark (13.40+/-2.49 and 12.19+/-2.85 mmHg, respectively). These results identify a day-night difference in bladder capacity and micturition frequency in chronically-instrumented nocturnal rodents that is phase-locked to the normal circadian locomotor activity rhythm of the animal. Furthermore, since it has generally been assumed that the daily hormonal regulation of renal function is a major driver of the circadian rhythm in urination, and few studies have addressed the involvement of the lower urinary tract, these results establish the bladder itself as a target for circadian regulation.